The Effect of Career Development and Compensation on Job Hopping of Millennial Employees with Employee Engagement as a Mediation Variable in Denpasar - Wayan Ristya Dewantari; Ida Bagus Raka Suardana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to understand the factors that influence the decision of millennial generation employees in Denpasar City to leave their jobs (job hopping). The main focus of the study is the influence of career development and compensation on job hopping with employee engagement as a mediating variable. Denpasar, the capital city of Bali Province and a rapidly growing economic center was chosen as the research location to explore this phenomenon among millennials, especially those aged between 28 and 43 years and who have had at least two working experiences. This study uses qualitative and quantitative data obtained through questionnaires distributed to respondents. The results of the study indicate that although the assessment of career development, compensation, and job-hopping variables is quite good, there is room for improvement, especially in the aspect of employee engagement and several elements related to compensation and career development. This study emphasizes the importance of career development and compensation in increasing employee engagement and reducing the tendency of job hopping among millennial employees in Denpasar City.